2006
DOI: 10.1590/s0103-84782006000200054
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de núcleos de Apis mellifera alimentados com suplemento aminoácido vitamínico, Promotor L®

Abstract: RESUMO Estudou-se o desenvolvimento na área de cria de 14 núcleos com quatro favos a partir da divisão de nove colméias de abelhas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 2 publications
1
3
0
5
Order By: Relevance
“…In this case, the energetic supplementation provided assisted in the maintenance of the colonies, and was able to explainthe greater number of brooding frames observed in the SS and IS treatments, suggesting that these energetic foods provided the necessary energetic support for the queen’s posture during this period. Castagnino et al (2006) obtained a large brooding area incolonies fed with sugar syrup, which was similar to the results of the present study. The energy provided by the consumption of the sugar syrup and inverted sugar probably stimulated the queen’s laying.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this case, the energetic supplementation provided assisted in the maintenance of the colonies, and was able to explainthe greater number of brooding frames observed in the SS and IS treatments, suggesting that these energetic foods provided the necessary energetic support for the queen’s posture during this period. Castagnino et al (2006) obtained a large brooding area incolonies fed with sugar syrup, which was similar to the results of the present study. The energy provided by the consumption of the sugar syrup and inverted sugar probably stimulated the queen’s laying.…”
Section: Discussionsupporting
confidence: 91%
“…Castagnino et al (2006) showed that energetic supplementation during the off-season increases the queen’s posture. In addition to supplying an energetic diet, a protein diet is also essential for colonymaintenance and improving the queen’s posture (Frias et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil quando se analisa a produção nacional, os produtores apresentam níveis variados de tecnologia e experiência prática, obtendo-se assim diferentes rendimentos produtivos (Martinez & Soares 2012 Keller et al, 2005). Assim, é necessário um substituto do pólen em períodos de escassez do pasto apícola, evitando oscilação na produção de geleia real (Castagnino et al, 2006;Pereira et al, 2006;Coelhoet al, 2008).…”
Section: Produção Da Geleia Real No Brasil E No Mundounclassified
“…A produção de geleia real e o desenvolvimento glandular é correlacionado fortemente com a quantidade de recurso proteico existente na colmeia (Pernal & Currie 2000;Keller et al, 2005). Assim, é necessário um substituto do pólen em períodos de escassez do pasto apícola, evitando oscilação na produção de geleia real (Castagnino et al, 2006;Pereira et al, 2006;Coelhoet al, 2008).…”
Section: Produção Da Geleia Real No Brasil E No Mundounclassified